ULTRASTRUCTURAL CHARACTERISTIC OF THE ADRENAL CORTEX WITH ACUTE ASEPTIC PERITONITIS AND ITS CORECTION WITH CRYOPRESERVED PLACENTA - Shepitʼko, V.I.; Skotarenko, T.A.; Yeroshenko, G.A.; Lisachenko, O.D. (World of Medicine and Biology, 2016)
In research conducted ultrastructural study of the zona fasciculata of the adrenal cortex with the introduction of cryopreserved placenta in the background of aseptic inflammation of the peritoneum. It was found, that aseptic peritonitis causes in the zona fasciculata of the adrenal cortex destructive changes, which occur on 3 day of observations degenerative changes of nuclei and organelles. To 7 days of the experiment destructive changes in the organelle determined. Introduction of the cryopreserved placenta on the background of the acute peritonitis causes an increase in lipid inclusions and minor degenerative changes of mitochondria on day 3, and prevents the occurrence of destructive changes in spongy-looking cells already on the 7th day of observation, which is manifested by reduction of the ultrastructure of mitochondria and endoplasmic reticulum.
Keywords: adrenal glands; spongy-looking cells; aseptic inflammation; cryopreserved placenta